2001
DOI: 10.1007/bf02344804
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviour of condenser microphone in mechanomyography

Abstract: Condenser microphones (MIC) have been widely used in mechanomyography, together with accelerometers and piezoelectric contact sensors. The aim of the present investigation was to clarify the mechanical variable (acceleration, velocity or displacement) indicated by the signal from a MIC transducer using a mechanical sinusoidal vibration system. In addition, the mechanomyogram (MMG) was recorded simultaneously with a MIC transducer and accelerometer (ACC) during voluntary contractions to confirm the mechanical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 26 publications
1
85
2
Order By: Relevance
“…Mathematically, each of the physical values of acceleration and displacement can be converted to the other's using integral or differential computation. Watakabe et al (2001) proved that the amplitude spectral density function (ASD) of the MIC is similar to the double integral of the ACC transducer signal, and suggested that the MIC acts as a displacement meter in the MMG. The MMG signals recorded by a MIC and an ACC showed differences in frequency response (Orizio, 1993;.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Mathematically, each of the physical values of acceleration and displacement can be converted to the other's using integral or differential computation. Watakabe et al (2001) proved that the amplitude spectral density function (ASD) of the MIC is similar to the double integral of the ACC transducer signal, and suggested that the MIC acts as a displacement meter in the MMG. The MMG signals recorded by a MIC and an ACC showed differences in frequency response (Orizio, 1993;.…”
Section: Discussionmentioning
confidence: 98%
“…However, the sensitivity of the MIC may be influenced by the size of its air chamber because the MIC detects the mechanical activity of the muscle via the air chamber. Watakabe et al (2001) proved in a mechanical vibration test that the sensitivity of frequency response did not change if the air chamber is at least 10 mm in diameter and 15 mm in length, though there existed a cut-off frequency of 2-4 Hz. In the present study we used an air chamber of 10 mm in diameter and 15 mm in length.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Piezoelectric contact sensors are mostly obsolete due their weight, and the applied pressure to obtain a mechanical coupling dampens the recorded MMG signal. Condenser microphones acting as a displacement meter are still used from time to time but they also require a coupling, e.g., air or gel between the muscle and the microphone (Watakabe et al, 2001). Further, the volume of the air-chamber influences the amplitude and the frequency content of the recorded MMG signal.…”
Section: Origin and Detection Of The Mechanomyogram Signalmentioning
confidence: 99%